Determining the Effectiveness of a Clinical Nursing Teaching Intervention in Improving Teamwork Ability: A Quasi-Experimental Study - Zhou YQ; Yang YL; Chen Y (Journal of Multidisciplinary Healthcare)
Yu-Qing Zhou, Yu-Ling Yang, Ying Chen Oncology Department, Affiliated Hospital of Jiangnan University, Wuxi, Jiangsu, 214122, People’s Republic of ChinaCorrespondence: Ying Chen, Email yki520@yeah.netObjective: This study aimed to explore the effectiveness of applying TeamSTEPPS ((Team Strategies & Tools to Enhance Performance & Patient Safety, TeamSTEPPS)) in clinical nursing education and evaluate its impact on improving teamwork skills among nursing trainees. TeamSTEPPS is a systematic framework developed to improve healthcare team performance and patient safety, focusing on core elements such as leadership, communication, situation monitoring, mutual support, and team structure.Methods: A total of 120 nursing trainees, who interned at Affiliated Hospital of Jiangnan University from November 2020 to November 2022, participated in this study. The participants were randomly divided into two groups: an intervention group (n= 60) that received instruction based on the TeamSTEPPS framework, and a control group (n= 60) that followed the traditional nursing education model. The TeamSTEPPS curriculum consisted of five key modules: team structure, effective communication, leadership, situation monitoring, and mutual support. The intervention included weekly theoretical and practical training sessions over a six-month period, incorporating group discussions, simulation training, scenario-based teaching, and role-playing. The impact of the intervention was assessed through pre- and post-intervention evaluations using the Teamwork Attitudes Questionnaire (T-TAQ), which measured teamwork awareness, communication skills, leadership, and mutual support.Results: Before the intervention, there were no significant differences between the two groups in terms of Team Structure, Leadership, Situation Monitoring, Mutual Support, and Communication skills (P > 0.05). After the intervention, the intervention group showed significant improvements in Team Structure, Leadership, Situation Monitoring, Mutual Support, and Communication skills, with scores significantly higher than those of the control group (P < 0.05).Conclusion: The TeamSTEPPS-based teaching model significantly enhances nursing students’ Team Structure, Leadership, Situation Monitoring, Mutual Support, and Communication skills, showing superior outcomes compared to the traditional education model. This evidence suggests that TeamSTEPPS is a valuable tool for nursing education and should be further promoted and applied in clinical training settings.Keywords: TeamSTEPPS, clinical nursing, teaching model, teamwork, teaching research